Income-contingent loans in higher education financing - Bruce Chapman; Lorraine Dearden (IZA World of Labor, 2022)
Around ten countries currently use a variant of a national income-contingent loans (ICL) scheme for higher education tuition. Increased international interest in ICL validates an examination of its costs and benefits relative to the traditional financing system, time-based repayment loans (TBRLs). TBRLs exhibit poor economic characteristics for borrowers: namely high repayment burdens (loan repayments as a proportion of income) for the disadvantaged and default. The latter both damages credit reputations and can be associated with high taxpayer subsidies through continuing unpaid debts. ICLs avoid these problems as repayment burdens are capped by design, eliminating default.
Keywords: I20; I21; I22; I23; I28; H42; 330; income-contingent loans; time-based repayment loans; consumption smoothing; default insurance; repayment burdens